Insignificant Events in the Life of a Cactus - Bowling, Dusti (New York Sterling Children's Books, 2017)
New friends and a mystery help Aden, thirteen, adjust to middle school and life at a dying western theme park in a new state, where her being born armless presents many challenges.
Keywords: People with disabilities -- Juvenile fiction; Amusement parks -- Juvenile fiction; Friendship -- Juvenile fiction; Adoption -- Juvenile fiction; Tourette syndrome -- Juvenile fiction; Overweight persons -- Juvenile fiction; Moving, Household -- Juvenile fiction; People with disabilities -- Fiction; Amusement parks -- Fiction; Friendship -- Fiction; Adoption -- Fiction; Tourette syndrome -- Fiction; Overweight persons -- Fiction; Moving, Household -- Fiction